Satisfaction of allergic patients treated with house dust mite sublingual immunotherapy. (May 2021) - Aarestrup, Matheus Fonseca; Aarestrup, Paula Fonseca; de Andrade, Mariana Senff; Aarestrup, Beatriz Julião V; Nagato, Akinori Cardozo; Aarestrup, Fernando Monteiro
Sublingual immunotherapy (SLIT) has been used for more than three decades as a therapeutic strategy for the treatment of allergic diseases. Studies have demonstrated its efficacy and safety, and numerous clinical trials have evaluated these parameters. In the present study, through patient perception, we investigated the patient satisfaction with the use of house dust mite SLIT treatment. "Satisfaction Scale for Patients Receiving Allergen Immunotherapy" (ESPIA) questionnaire, a standardized and validated instrument for clinical studies evaluating allergen immunotherapy, was applied to allergic patients ( N = 136). Children and adults of both sexes who received SLIT for Dermatophagoides pteronyssinus and/or Blomia tropicalis, according to the results of an immediate reading puncture test, were included. Data analysis showed that the perception of treatment effectiveness was 92%, performance improvement in the daily activities was 91%, a satisfactory cost-benefit balance was 84%, and the perception of general satisfaction was 97%. The results showed a high perception of satisfaction in allergic patients undergoing house dust mite SLIT.